Pediatric logistic organ dysfunction score as a predictive tool of dengue shock syndrome outcomes - Lola Purnama Dewi; Eka Nurfitri (Indonesian Pediatric Society, 2012)
Background The pediatric logistic organ dysfunction (PELOD)score is widely used as a predictive tool of patient outcomesin pediatrics intensive care unit (PICU) settings, includingfor dengue shock syndrome (DSS) patients. We evaluated thepredictive value of PELOD scores in DSS patients taken withinthe first hours after PICU admission.Objective To evaluate the usefulness of PELOD scores takenin day 1 of PICU admission for predicting outcomes in DSSpatients.Methods We included 81 DSS subjects admitted to the PICUbetween April 2006 - October 2009 by consecutive sampling.There were 12 children under 12 months of age, 48 children 1- 5years of age, and 21 children above 5 years of age enrolled in thestudy. PELOD calculations were performed as set out by originalarticles, using the published formula.Results0fthe81PICUpatients,15 (18.5%) died. The estimated,predicted mortality using PELOD scores were 43% for infantsunder 12 months, 12% for children 1 - 5 years, and 10% forchildren above 5 years. The actual mortality rates were 58.3%(7 subjects) for infants under 12 months, 10.4% (5 subjects) forchildren 1-5 years, and 14.3% (3 subjects) for children above 5years. In patients who died, PELOD indicated the most commonorgan problems to be hepatic disorders (SGOT/SGPT > 950 IU!L)and haematologic disorders (prothrombin time, INR > 1.65) in 8(53.3%) subjects and 9 (60%) subjects, respectively.Conclusion PELOD scores from subjects taken on day 1 of PICUadmission can be used to predict mortality outcome. [Paediatrlndones. 2012;5 2: 72-7].